The swailing - Errington, Patrick James (Hugh MacLennan poetry series., 2023)
"Firmly rooted in fire-haunted landscapes that are at once psychological, emotional, and fiercely real, Patrick James Errington's first collection traces the brittle boundaries between presence and absence, keeping and killing, cruelty and tenderness. In these poems human voices whisper through the natural world - a hand turns on a lamp to extinguish the stars; stones outline a sleeping form; a black eye is a storm cloud. Errington stokes vivid images, formal grace, and subtle humour into the flickers of life that hold fast against unforgiving terrain. Here language functions like a controlled burn, one that could at any moment preserve, perfect, or reduce to ash. Urgent, resonant to the bone, the swailing burns to the ember-edge of grief, memory, and control to find the wildness, wilderness, and wonder that remain. "Like figures walking through the smoke from a burning field, Errington's poems emerge with remarkable definition, clarity, and surprise." Bronwen Wallace Prize jury citation"--